(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study was conducted to ascertain the employability skills required of office technology and management (OTM) graduates by small scale enterprises in Anambra State. The study adopted a descriptive Survey design. Two research questions guided the study, while two hypotheses were tested at 0.05 level of significance. Population of 980 mangers of small scale enterprise was used for the study. Proportionate stratified sampling techniques were used to sample 294 small scale enterprise managers in Anambra State. The questionnaire was validated by experts in business education. The reliability method was used to determine the reliability of the instrument was established using Cronbach alpha formula to determine the internal consistency of the instrument which yielded Correlation coefficient values of 0.93, 0.97, 0.98, and 0.96 for the four clusters of the questionnaire, with the overall coefficient value of 0.96. Mean was used to answer the research questions while the null hypothesis were tested at 0.05 level of significance using Ztest. Data collected were analyzed using arithmetic mean and standard deviation to answer the research questions. Findings from the study revealed that problem solving skill, and database administration skills, are highly required of OTM graduates by small scale enterprises in Anambra State.